Variation in veterans affairs hospitals’ UV-C surface disinfection systems guidance documents: a qualitative content analysis - Julia Friberg Walhof; AM Racila; Stacy Hockett Sherlock; Cassie Cunningham Goedken; Daniel Suh; Bernardino Guerrero; Trina Zabarsky; Kimberly Dukes; Eli N Perencevich (Antimicrobial Stewardship & Healthcare Epidemiology)
The Department of Veterans Affairs (VA) does not have system-wide standardized policies or procedures for ultraviolet-C (UV-C) use. Qualitative researchers performed content analysis of VAV UV-C guidance documents. We observed that lack of specificity and uniformity across guidance documents is a potential barrier to UV-C implementation and future quality control.